Intraocular medulloepitheliomas and embryonal tumors with multilayered rosettes of the brain: comparative roles of LIN28A and C19MC - Jakobiec, Frederick A.; Pfister, Stefan (American journal of ophthalmology, 2015)
Purpose: To compare immunohistochemical and genetic overlaps and differences between intraocular medulloepitheliomas and embryonal tumors with multilayered rosettes of the brain. Design: Retrospective histopathologic, immunohistochemical, and genetic analysis of 20 intraocular medulloepitheliomas. Methods:(1) Review of clinical data and hematoxylin-eosin-stained sections with (2) immunohistochemical staining of paraffin sections using a polyclonal antibody against the protein LIN28A, and (3) fluorescence in situ hybridization (FISH) testing for the amplification of the genetic locus 19q13.42 involving the C19MC cluster of miRNA. Ten retinoblastomas served as controls and to determine the specificity of these biomarkers for intraocular medulloepitheliomas. Results: Nineteen of the 20 intraocular medulloepitheliomas were either diffusely or focally LIN28A positive (weak, moderate, or strong). The most intense positivity correlated with aggressive behavior such as intraocular tissue invasion or extraocular extension. None of the cases studied by FISH harbored an amplicon for C19MC. The 10 retinoblastomas were LIN28A and C19MC negative. Conclusion: LIN28A has a putative role in oncogenesis and is found only in embryonic cells and malignancies. Intraocular medulloepitheliomas and embryonal tumors with multilayered rosettes of the brain both display LIN28A positivity. Only the latter, however, display amplification of the 19q13.42 locus involving C19MC, implying that other causative factors are at play in intraocular medulloepitheliomas. More aggressive tumor behavior within the eye can be partially predicted by LIN28A staining intensity.